2012
DOI: 10.1038/srep00643
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of a Normal Human Cell Traversed by a Single Charged Particle

Abstract: The long-term “fate” of normal human cells after single hits of charged particles is one of the oldest unsolved issues in radiation protection and cellular radiobiology. Using a high-precision heavy-ion microbeam we could target normal human fibroblasts with exactly one or five carbon ions and measured the early cytogenetic damage and the late behaviour using single-cell cloning. Around 70% of the first cycle cells presented visible aberrations in mFISH after a single ion traversal, and about 5% of the cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…In addition, a connection between elevated levels of ROS, an impeded oxidative defense and the accumulation of chromosomal damage has been reported in X-irradiated human tumor cells [ 10 ]. In foreskin fibroblasts (AG1522), however, an increased long-term chromosomal instability was not observed in our previous studies [ 18 , 19 ]. Therefore, we addressed the question of whether increased ROS levels occur in AG1522 fibroblasts that do not show chromosomal instability.…”
Section: Introductionmentioning
confidence: 60%
“…In addition, a connection between elevated levels of ROS, an impeded oxidative defense and the accumulation of chromosomal damage has been reported in X-irradiated human tumor cells [ 10 ]. In foreskin fibroblasts (AG1522), however, an increased long-term chromosomal instability was not observed in our previous studies [ 18 , 19 ]. Therefore, we addressed the question of whether increased ROS levels occur in AG1522 fibroblasts that do not show chromosomal instability.…”
Section: Introductionmentioning
confidence: 60%
“…As highlighted in Table and the corresponding discussion, RBE effects are believed to arise as a result of DSB interactions in molecular and cellular targets and the ionization density along the trajectory of an ion (i.e., the track structure) and among cells. Focused particle microbeams are a potentially effective way to probe the interaction of the DSB formed along different particle tracks. For example, Girst et al .…”
Section: Model Testing and Clinical Validation Of Rbe Modelsmentioning
confidence: 99%
“…As highlighted in Table IV and the corresponding discussion, RBE effects are believed to arise as a result of DSB interactions in molecular and cellular targets and the ionization density along the trajectory of an ion (i.e., the track structure) and among cells. Focused particle microbeams [152][153][154][155][156][157][158][159] are a potentially effective way to probe the interaction of the DSB formed along different particle tracks. For example, Girst et al 160 used live-cell observations and distance tracking of the GFP-tagged DNA damage response protein MDC1 to study the random-walk behavior of DSB formed in chromatin domains by 20 MeV proton and 43 MeV carbon ions.…”
Section: Model Testing and Clinical Validation Of Rbe Modelsmentioning
confidence: 99%
“…The occurrence of IR-induced instability was shown to be further delayed in late passages after irradiation with higher LET IR [91,92]; therefore, it can be concluded that high-LET IR has a higher capacity to induce delayed genomic instability compared to low-LET IR [102]. Furthermore, long-term instability can even be induced by a single alpha-particle [103] or carbon ion [104] from a focused microbeam, as well as following cytoplasmic irradiation with alpha particles [105,106]. Eventually, these IR-induced or pre-existing recessive mutations may be unmasked and amplified, and upon loss of tumor suppressor function, those cells that harbor genetic alterations that give them a proliferative advantage invade the cell population.…”
Section: Telomere Maintenance and The Effects Of Ionizing Radiationmentioning
confidence: 99%